Nosocomial infections and staff hygiene - Dimitra Petroudi (Journal of Infection in Developing Countries)
Nosocomial infections are a major source of morbidity and mortality in hospital settings. The most important defences against nosocomial transmission of viral, bacterial, and other infections are detailed and continuing education of staff and strict adherence to infection control policies. The issue is no longer whether hand hygiene is effective, but how to produce a sustained improvement in health workers' compliance.